Reviews. Guy Puzey and Laura Kostanski (eds.), Names and Naming: People, places, perceptions and power (Bristol: Multilingual Matters, 2016), 258 pp. ISBN 9781783094905. (2019) - Cuthbertson, Katherine
No abstract available